Continuous Genetic Assessment of the Impact of Hatchery Releases on Larimichthys crocea Stocks in China - Lina Wu; Lisheng Wu; Hungdu Lin; Min Liu; Shaoxiong Ding (Global Ecology and Conservation)
As a cornerstone species in China's nearshore marine fisheries, Larimichthys crocea has experienced severe population declines due to the exploitation of its spawning and overwintering aggregations. In response, the Chinese government authorities have implemented extensive restocking programs over the past three decades, particularly in Fujian waters. However, the direct evidence of population recovery remains limited, and the genetic impact of large-scaled, hatchery-produced juvenile releases on wild stocks is unclear. In this study, we analyzed hatchery-released stocks (HRS), and wild-captured stocks in the semi-closed Sansha Bay (SBS, northern Fujian) and in the open waters of southern Fujian (SFS) over four consecutive years (2020–2023) using microsatellite markers. Our results reveal the significant genetic differentiation and distinct contribution rates between SBS and SFS, highlighting the region-specific impacts of restocking. The high genetic similarity between SBS and HRS suggests that the Bay may provide favorable conditions for the survival of released stocks compared to open waters. Seasonal genetic variation observed in SBS stocks before and after winter, along with interannual differences in contribution rates, underscoring the winter season is a critical survival bottleneck. The findings of this study indicate that HRS face greater challenges than wild stocks in completing overwinter migrations. These insights provide valuable guidance for the conservation and management of L. crocea stocks, and emphasize the importance of integrating ecological and environmental factors into restocking strategies for this and other marine species.